Determination of clinical state of hepatitis B virus infection of patients in Basra governorate: Saad S. Hamadi1 , Hayder A. Al-Hmoudi2 and Awatif H. Issa2 - Hamadi, Saad S. (The Iraqi Journal of Veterinary Medicine, 2012)
Hepatitis B virus is a hepatotropic virus that causes acute and chronic hepatitis, livercirrhosis and hepatocellular carcinoma; it is responsible for more than one million deathsannually worldwide despite hepatitis B vaccination. So, the aim of the present study was todetect the total markers of HBV (HBsAg, HBsAb, HBeAg, HBeAb, Total anti-HBc and IgManti-HBc) .A total of 126 cases with hepatitis B were recruited from different medical centersin Basra. Serological tests were preformed for all cases using ELISA tests. 126 patients weredivided into 8 studied groups including: Incubation, Active acute, Acute, Active chronic,chronic, Inactive HBsAg Carrier, HBsAg-negative patients and liver cancer. We conclude thatthe vast majority of patients were Inactive HBsAg Carrier (54.76 %) fallowed by acutehepatitis (16.67 %) and HBsAg-negative patients (7.14 %).